2022
DOI: 10.1007/s11896-022-09542-6
|View full text |Cite|
|
Sign up to set email alerts
|

Are Current Drug Driving Enforcement Strategies Achieving the Desired Effect? Drug Users’ Perceptions of Drug Driving Legislation and Enforcement in Queensland

Abstract: This study examined how illicit drug users perceived roadside drug testing (RDT) in Queensland, a jurisdiction that enforces a zero-tolerance enforcement strategy to drug driving. Fifty-two illicit drug users were interviewed, and thematic analysis was used to identify emerging themes. The results showed that exposure to RDT and apprehension certainty were reportedly low. The targeted regime of RDT had dichotomous implications towards apprehension certainty, due to the familiarity with the testing procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Around half of the sample considered the risk of apprehension for drug driving to be likely (to some extent) which differs to similar Queensland‐based studies where participants perceived the likelihood to be low [16, 18]. One in four participants reported using a police avoidance strategy to reduce the likelihood of detection, with Facebook police location sites most used (16% of sample).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Around half of the sample considered the risk of apprehension for drug driving to be likely (to some extent) which differs to similar Queensland‐based studies where participants perceived the likelihood to be low [16, 18]. One in four participants reported using a police avoidance strategy to reduce the likelihood of detection, with Facebook police location sites most used (16% of sample).…”
Section: Discussionmentioning
confidence: 78%
“…However, the high level of drug driving in the present sample suggests there may be a greater cost to not supplying guidelines to those who use cannabis. In the absence of such information, individuals using cannabis are likely to make their own decisions, driving at a time they believe they are safe to drive [18], assessments which are often incorrect [13]. The authors acknowledge the current challenges with implementing guidelines (including the variable nature of cannabis impairment and the enforcement of such guidelines).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same effect is yet to be observed for driving under the influence of drugs and roadside drug-testing operations. In fact, recent studies have found a considerable proportion of drug takers report behaviors such as driving under the influence of drugs (Arkell et al, 2020; Love et al, 2024; Mills, Freeman, et al, 2022) and perceive the likelihood of detection for driving under the influence of drugs to be low (Love et al, 2024; Mills, Freeman, et al, 2022).…”
Section: Deterrence Theorymentioning
confidence: 99%